Segni di futuro: immagini di migrazioni e mutamento nei territori del Sud Italia. Riflessioni sull’uso dei metodi visuali nella ricerca sociale - Peruzzi, Gaia; Lombardi, Raffaele (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2020)
Migrations are one of the most powerful factors in the history of humankind and transform societies. Southern Italy, which has been for years the destination of huge fluxes, is a privileged European observatory for such transformations. The contribution discusses the results of a research-action developed in Southern Italy in 2016. Segni di futuro is a project involving Third sector managers in a research laboratory with the aim to identify the signs of current transformations and the symptoms of future ones. The points of strength of the research, which has been lead with strate- gies and techniques of visual sociology, consist in a reflection on methods on visual research and on the social construction of the point of view.